P110α of PI3K is necessary and sufficient for quiescence exit in adult muscle satellite cells. (26th March 2018) - Wang, Gang; Zhu, Han; Situ, Chenghao; Han, Lifang; Yu, Youqian; Cheung, Tom H; Liu, Kai; Wu, Zhenguo
Abstract: Adult mouse muscle satellite cells (MuSCs) are quiescent in uninjured muscles. Upon injury, MuSCs exit quiescence in vivo to become activated, re‐enter the cell cycle to proliferate, and differentiate to repair the damaged muscles. It remains unclear which extrinsic cues and intrinsic signaling pathways regulate quiescence exit during MuSC activation. Here, we demonstrated that inducible MuSC‐specific deletion of p110α, a catalytic subunit of phosphatidylinositol 3‐kinase (PI3K), rendered MuSCs unable to exit quiescence, resulting in severely impaired MuSC proliferation and muscle regeneration. Genetic reactivation of mTORC1, or knockdown of FoxO s, in p110α ‐null MuSCs partially rescued the above defects, making them key effectors downstream of PI3K in regulating quiescence exit. c‐Jun was found to be a key transcriptional target of the PI3K/mTORC1 signaling axis essential for MuSC quiescence exit. Moreover, induction of a constitutively active PI3K in quiescent MuSCs resulted in spontaneous MuSC activation in uninjured muscles and subsequent depletion of the MuSC pool. Thus, PI3K‐p110α is both necessary and sufficient for MuSCs to exit quiescence in response to activating signals. Synopsis: A signalling pathway connecting phosphatidylinositol 3‐kinase subunit p110‐alpha (PI3K‐p110α), mTORC1 and the transcription factor c‐Jun is essential for the exit of adult mouse muscle satellite cells (MuSCs) from quiescence upon tissue injury. Inducible MuSC‐specific deletion of the catalytic PI3K‐p110α in vivo renders MuSCs unable to exit quiescence, resulting in severely impaired proliferation and muscle regeneration. Genetic reactivation of mTORC1 by co‐deletion of Tsc1 partially rescues the defects in p110α‐null MuSCs. Transcript levels of several AP‐1 family members ( c‐Jun, Fos, and Fosb ) fail to be induced in p110α‐null MuSCs during injury or isolation, and re‐expression of c‐Jun restores proliferation in the mutant MuSCs. Constitutive MuSC‐specific activation of PI3K‐p110α in adult mice results in spontaneous quiescence exit and depletion of the MuSC pool. Abstract : Phosphatidylinositol 3‐kinase (PI3K)–mTORC1–c‐Jun signaling is essential for muscle stem cell quiescence exit and tissue repair upon injury.